2022
DOI: 10.5772/intechopen.108592
|View full text |Cite
|
Sign up to set email alerts
|

Talaromyces marneffei Infection: Virulence Factors and Rapid Diagnostics

Abstract: Talaromyces (Penicillium) marneffei is a thermally dimorphic fungus that causes talaromycosis, and the pathogen is found throughout tropical and subtropical Asia. T. marneffei has specifically emerged as an opportunistic fungal pathogen in individuals with advanced HIV disease and, to a lesser extent, other immunocompromised conditions, but more recently talaromycosis is increasingly described in immunocompetent people. Due to the high mortality rate of up to 50%, understanding T. marneffei interactions with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 136 publications
1
1
0
Order By: Relevance
“…21 Melanin is important for the virulence of T. marneffei by protecting it from solar, UV or gamma radiation. 22 In addition, it is also recognized as an antifungal resistance factor 23 and able to make T. marneffei resistant to antifungals including amphotericin B. 24 On the other hand, the majority of the studies including Sar et al 18 and Sekhon et al 20 reported low GM MIC of itraconazole, ≤0.5 µg/mL, against yeast and mold forms which is similar to this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…21 Melanin is important for the virulence of T. marneffei by protecting it from solar, UV or gamma radiation. 22 In addition, it is also recognized as an antifungal resistance factor 23 and able to make T. marneffei resistant to antifungals including amphotericin B. 24 On the other hand, the majority of the studies including Sar et al 18 and Sekhon et al 20 reported low GM MIC of itraconazole, ≤0.5 µg/mL, against yeast and mold forms which is similar to this study.…”
Section: Discussionsupporting
confidence: 82%
“…21 Melanin is important for the virulence of T. marneffei by protecting it from solar, UV or gamma radiation. 22 In addition, it is also recognized as an antifungal resistance factor 23 and able to make T. marneffei resistant to antifungals including amphotericin B. 24 …”
Section: Discussionmentioning
confidence: 99%